Further processed according to journal proceduresThe Effect of Providing Sports Massage on Physical Fitness in Karate Martial Arts Athletes of SMA 2 Praya - Herlina, Herlina; Burhan, Zakir; Ashari, Lalu Hasan; Ripai, Agus Sari M. (JUPE : Jurnal Pendidikan Mandala, 2025)
Karate is one of the martial arts in Indonesia that is competed internationally. One of the kicking techniques in karate is the mawashi geri kick. In martial arts, the frequency of this kick is very important. This technique, if it hits the target quickly and accurately, will result in 3 points in one mawashi geri kick. This study aims to prove the provision of sport massage for karate athletes in order to improve fitness and accuracy in mawashi geri kicks in karate athletes at Dojo SMAN 2 Praya. Muscle tension is part of the symptoms of Delayed Onset Muscle Soreness (DOMS), and is usually complained of by athletes after 12-24 hours of high-intensity training. Muscle tension can be overcome with various methods, one of which is using the sport massage method to relax muscle tension that occurs in karate athletes at Dojo SMA 2 Praya. This study is experimental with a pre-test and post-test control group design, conducted at SMA 2 Praya. The research subjects were 16 people where the researcher will conduct a test before and after being given a sports massage to determine the extent of the effect of giving sports massage on the physical fitness of karate dojo athletes at Sma 2 Praya. Hypothesis testing was carried out using the t-test (independent samples test). In accordance with the hypothesis testing, if t count> t table then H0 is rejected and Ha is accepted. Likewise, if t count <t table then H0 is accepted and Ha is rejected.